Development of Electromagnetic-Based Physical Pendulum Practical Tools Using Infrared Sensors - Bachtiar, Armando; Ermawati, Imas Ratna (Jurnal Penelitian Pembelajaran Fisika, 2025)
Abstract. Basic physics practicums often face measurement accuracy constraints due to limited tools and human error. This study aims to develop an electromagnetic-based physical pendulum practicum tool using an infrared sensor and measure its feasibility in basic physics practicum lectures 1. The method used is Research and Development (R&D) with a descriptive quantitative approach and a 3D development model. The data analysis technique uses a Likert scale with a range of 1-5 which is converted into quantitative data to calculate the percentage of feasibility. From the results of the needs analysis, 72.2% of students had difficulty in manually collecting data and supported the development of the tool. The results showed that the practicum tool was declared feasible based on the assessment of media experts with a percentage of 90% included in the very good category. Then the assessment from material experts showed a percentage of 91% included in the very good category. It can be concluded that the electromagnetic-based physical pendulum practicum tool using an infrared sensor is feasible for use in basic physics practicum activities 1 and can help overcome students' difficulties in collecting data. This study contributes to the development of electromagnetic and sensor-based technological innovations to improve the accuracy of physics practicum measurements and reduce measurement errors.